Glossopharyngeal Nerve Regeneration Is Essential for the Complete Recovery of Quinine-Stimulated Oromotor Rejection Behaviors and Central Patterns of Neuronal Activity in the Nucleus of the Solitary Tract in the Rat - King, Camille T. (J Neurosci, 2000)
The peripheral, central, and behavioral consequences of glossopharyngeal nerve transection (GLX), regeneration, and the prevention of regeneration on the quinine-elicited responses of adult rats were concurrently examined. Oromotor taste reactivity (TR) was videotaped during intraoral infusion of 7 ml of either quinine (3 mm) or distilled water at 17, 52, or 94 d after surgery. We confirmed previous findings by showing that 17 d after neurotomy, (1) the number of circumvallate (CV) and foliate taste buds, (2) gapes (a characteristic aversive TR response), and (3) the number of Fos-like immunoreactive (FLI) neurons in the gustatory NST (gNST), particularly in the medial portion (subfield 5) of the rostral central subdivision (RC), were all severely attenuated in GLX rats. We extended these findings by showing that these lesion-induced effects were enduring when the GL did not regenerate (up to 94 d). In contrast, when the GL regenerated, as few as 52 d were sufficient to re-establish quinine-elicited TR, especially gaping, and FLI expression in RC, particularly within subfield 5, to values comparable with quinine-stimulated sham-operated rats. Evidently, the gNST maintains its potential to restore accurately the organization of neural activity that is disrupted by nerve injury, as assessed by FLI, ultimately leading to the return of normal protective oromotor responses, provided the nerve regenerates. This recovery was complete despite the reappearance of a reduced population of CV taste buds (∼75% control values) and may relate to peripheral and/or central changes that occur in tandem with regeneration of the GL.